Analisis Realiasi Penerimaan Program Bantuan Pemerintah terhadap Kemiskinan di Desa Lumban Tobing, Kecamatan Doloksanggul - Cinta , Gia; Simamora, Vailimlim; Kuntuy, Jacob; Kemala Dewi, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Lumban Tobing Village, Doloksanggul District is located in North Sumatra Province which is the capital of Humbang Hasundutan Regency in Indonesia. The variations quality of life conditions in Lumbang Tobing Village causes variations in poverty conditions in this area. This research aims to determine the condition of poverty in Lumban Tobing Village and formulate a comprehensive poverty program hatching program in Lumban Tobing Village. The method used in this research is descriptive research using a qualitative approach. By using as many as 19 family cards, subjects or as many as 254 families receiving aid were recorded. Research conditions show that poverty conditions in Lumban Tobing Village vary due to different livelihoods, age levels of household heads and limited human resources. The method of poverty in question is the provision of subsidy program assistance in the form of BLT, BST, BPNT, PHK and basic food supplies.